Quasi‐Antiphase Diel Patterns of Abundance and Cell Size/Biomass of Picophytoplankton in the Oligotrophic Ocean - Li, Changlin; Chiang, Kuo‐Ping; Laws, Edward A.; Liu, Xin; Chen, Jixin; Huang, Yibin; Chen, Bingzhang; Tsai, An‐Yi; Huang, Bangqin (Geophysical research letters, 2022)
Picophytoplankton are the smallest, most abundant photosynthetic organisms in the ocean. Knowledge of the diel variability of these tiny microbes has important implications for the structure of microbial food webs and key biogeochemical processes. However, insight into the mechanisms that underlie picophytoplanktonic diel dynamics is limited. By combining a field survey with a published dataset, we found that cell numbers and cell sizes/biomasses of picophytoplankton were tightly synchronized to the day‐night cycle, but they were in a quasi‐antiphase relationship to each other. This pattern is a confirmation and extension of previous studies. Mortality rates showed that Prochlorococcus and Synechococcus were subject to considerable grazing pressure throughout the day and night. The quasi‐antiphase diel cycles in abundance and cell size/biomass are likely determined by the light‐dependent diel behavior of cell growth and division and continuous losses to grazing. This work significantly improves our understanding of autotrophic picoplankton in the oligotrophic ocean. Plain Language Summary Picophytoplankton are tiny, single‐celled photosynthetic organisms that contribute to almost all primary production in the vast euphotic zones of the oligotrophic ocean. Understanding their roles in that environment is critical but challenging, mainly because of their minuscule size and the complexity of microbial processes and interactions. Time‐series observations based on flow cytometry, a powerful technique that provides information about the numbers and sizes of picophytoplankton cells, have elucidated many ecological and biogeochemical processes associated with picophytoplankton, but some questions remain. A field survey in the northern South China Sea combined with a published dataset revealed that picophytoplankton cell size and biomass tended to decrease (increase) during the night (day) when cell numbers were increasing (decreasing). Such quasi‐antiphase cycles are likely a general feature of near‐steady‐state oligotrophic ecosystems and reflect the cycles of carbon fixation, energy storage, and cell growth during the daytime and cell division and energy depletion during the night. Mortality rates estimated via modified dilution experiments showed that Prochlorococcus and Synechococcus were subject to considerable grazing pressure throughout the day and night. This work significantly improves our understanding of these microorganisms and may have implications for the carbon cycle in oligotrophic marine ecosystems. Key Points Picophytoplanktonic quasi‐antiphase diel cycles in abundance and cell size/biomass are likely a general feature of the oligotrophic ocean Grazing pressure on Prochlorococcus and Synechococcus is as high during the day as during the night